A Comparative Analysis of Investment Feasibility in the Financial Sector Stocks Across ASEAN Countries Using the CAPM - Muktar Redy Susila; Wawan Cahyo Nugroho; Dian Arini (E-Jurnal Akuntansi, 2025)
Financial sector stocks constitute a dominant presence in the capital markets of ASEAN countries. These stocks are characterized by high volatility and considerable investment risk. This study aims to evaluate the performance of financial sector stocks in selected ASEAN countries, namely Vietnam, Thailand, Singapore, Indonesia, the Philippines, and Malaysia. The sample includes financial sector stocks that have been consistently listed on each country’s stock exchange from January 2020 to June 2024. The selection criteria include companies within the financial sector that rank among the top five in market capitalization within their respective national financial sector indices. The Capital Asset Pricing Model (CAPM) is employed as the primary method for assessing investment feasibility. The CAPM analysis reveals that not all financial sector stocks in ASEAN countries are efficient. In particular, financial sector stocks in the Philippines and Singapore are found to be entirely inefficient, whereas those in Thailand are categorized as efficient. The investment feasibility outcomes for the remaining ASEAN countries demonstrate varying results. Statistical testing yields a significance value (p-value) of less than 0.05, indicating significant differences in the investment feasibility of financial sector stocks across ASEAN nations.These findings underscore the heterogeneous performance of financial sector stocks within the ASEAN region, highlighting the need for country-specific investment analysis and risk assessment.